Efektivitas Penggunaan Multimedia Pembelajaran Powerpoint terhadap Peningkatan Motivasi dan Hasil Belajar Siswa - Karimah, Iik; Hamdani, Agus; Nurwahidah, Lina Siti; Damayanti, Deasy Aditya (JOEAI (Journal of Education and Instruction), 2023)
This study aims to determine the effectiveness of the use of PowerPoint learning multimedia on increasing motivation and student learning outcomes in the Indonesian language subject in class XII IPS 2 MA Daarul Abroor Tasikmalaya. The method used is pre-Experimental Design. With the form of One-Group Pretest-Postest Designs, which compares the results of the pre-test and post-test. The sample of this research was 32 students, namely class XII IPS 2 MA Daarul Abroor Tasikmalaya. Researchers used data collection techniques in the form of pre-test and post-test. From the results of this study, the following conclusions were obtained: (1) The use of PowerPoint learning multimedia was effective in increasing student motivation in Indonesian language subjects in Class XII IPS 2 MA Daarul Abroor Tasikmalaya. This is proven by the Wilcoxon Test that z = -4.940 and the value of Asym.Sig (2-tailed) -0.000 because the resulting value of Asym.Sig (2-tailed) is smaller than the alpha used, which is 0.05, then Ho is rejected or Ha accepted; and (2) The use of PowerPoint learning multimedia is effective in improving student learning outcomes in the Indonesian language subject in Class XIl IPS 2 MA Daarul Abroor Tasikmalaya. This is proven by the Wilcoxon Test, the value of z = -4.939 and the value of Asym.Sig (2-tailed) = 0.000 because the resulting value of Asym.Sig (2-tailed) is smaller than the alpha used, which is 0.05, then Ho is rejected or Haha accepted. This study concluded that the use of PowerPoint learning multimedia effectively had a significant influence on the motivation and learning outcomes of class XII IPS 2 MA Daarul Abroor Tasikmalaya. Keywords: Multimedia, Learning, Powerpoint, Motivation, Learning Outcomes